2013
DOI: 10.4088/jcp.12r07967
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Prenatal Antidepressant Exposure on Neonatal Adaptation

Abstract: An increased risk of PNAS exists in infants exposed to antidepressant medication during pregnancy; respiratory distress and tremors also show associations. Neonatologists need to be prepared and updated in their management, and clinicians must inform their patients of this risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
108
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(114 citation statements)
references
References 42 publications
2
108
0
4
Order By: Relevance
“…Occurring in 15% to 30% of infants, these symptoms are most often time-limited (typically resolving in 2-14 days), are not associated with an increased risk of mortality or longer-term neurodevelopmental problems, and resolve with supportive care. 64 This risk may be highest with paroxetine, venlafaxine, and fluoxetine. 64 Limited data also suggest that SSRIs taken late (but not early) in pregnancy may be associated with an increased risk of persistent pulmonary hypertension of the newborn (PPHN).…”
Section: What Are the Risks Of Using Antidepressant Medications In Prmentioning
confidence: 99%
See 1 more Smart Citation
“…Occurring in 15% to 30% of infants, these symptoms are most often time-limited (typically resolving in 2-14 days), are not associated with an increased risk of mortality or longer-term neurodevelopmental problems, and resolve with supportive care. 64 This risk may be highest with paroxetine, venlafaxine, and fluoxetine. 64 Limited data also suggest that SSRIs taken late (but not early) in pregnancy may be associated with an increased risk of persistent pulmonary hypertension of the newborn (PPHN).…”
Section: What Are the Risks Of Using Antidepressant Medications In Prmentioning
confidence: 99%
“…64 This risk may be highest with paroxetine, venlafaxine, and fluoxetine. 64 Limited data also suggest that SSRIs taken late (but not early) in pregnancy may be associated with an increased risk of persistent pulmonary hypertension of the newborn (PPHN). The absolute risk is 2.9 to 3.5 per 1000 infants compared to a general population risk of 2 per 1000.…”
Section: What Are the Risks Of Using Antidepressant Medications In Prmentioning
confidence: 99%
“…In observational studies, antidepressant use has been shown to increase the risk of different adverse outcomes, such as spontaneous abortion, 12 preterm birth, 13 low birth weight, 13 major congenital malformations, 14 postpartum hemorrhage, 15 poor neonatal adaptation syndrome, 16 persistent pulmonary hypertension of the newborn, 17 autism, 18 and others. There are no RCTs available that examine the safety of antidepressant use in pregnant depressed women, and it is unlikely that such RCTs will be conducted in the foreseeable future.…”
Section: Parallels In Psychiatric Literature: Examplementioning
confidence: 99%
“…In contrast, we identified a statistically and clinically significant increase in risk for poor neonatal adaptation syndrome associated with antenatal antidepressant exposure, as well as associations with the specific signs of respiratory distress and tremors. 10 These findings suggest a potential role for neonatologists in monitoring and caring for infants exposed to antidepressants in utero. Finally, our analyses reveal that antenatal maternal depression is associated with increased risk for premature delivery and lower rates of breastfeeding initiation, although in both cases, the odds ratios are relatively small.…”
mentioning
confidence: 97%
“…We developed a quality assessment tool, the Systematic Appraisal of Quality in Observational Research 8 to evaluate each article and performed meta-analyses when possible. Three systematic reviews and meta-analyses resulting from this work appear in JCP's Online Exclusives this month and include the following outcomes: congenital malformations 9 (including cardiac), poor neonatal adaptation, 10 and the impact of maternal depression on various outcomes (including premature delivery, gestational age, birth weight, low birth weight, neonatal intensive care unit admissions, Apgar scores, preeclampsia, and breastfeeding initiation).…”
mentioning
confidence: 99%